(untitled) (UNIZIK Journal of Agricultural Economics and Extension, 2024)
The study examined effect and economic rejuvenation strategies in palm oil processing during and post COVID-19 in Irele Local Government Area, Ondo State. Multistage sampling technique was employed in the selection of 215 respondents for the study. Data were collected using structured questionnaire and responses were collated and analyzed using descriptive statistics and regression analysis. Findings revealed that threshing of bunch was the most tedious activities experienced during palm oil processing and that COVID-19 affected the operational activities of palm oil processing as the lockdown hindered major operational activities of palm oil, as well as caused a total pause of operational activities of palm oil processing. In addition, the gross margin during COVID-19 in 2020 was N435,000.00 and the post COVID-19 gross margin in 2023 was N565,000.00. Regression result indicated that household size (p< 0.001), processing experience (p< 0.001), labour (p< 0.05) and threshing cost (p< 0.001) have positive coefficients and are statistically significant factors that contributed to profit in palm oil processing. The study therefore recommended that farmers should be encouraged to form co-operative societies to solve the problems of inadequate information and cultivation knowledge as well as give the avenue for earnest government intervention measures in case of any outbreak or crises.